Pengaruh Sosial Media Marketing, Brand Ambassador dan Kualitas Produk Terhadap Minat Beli Ulang Mahasiswa Semarang pada Produk Skincare the Originote - Abaya Linggar Nirwanda; Suhaji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the influence of social media marketing, brand ambassadors, and product quality on the repurchase intention of Semarang students toward The Originote skincare products. The findings are expected to help the company in developing effective marketing strategies. This study employs a quantitative research method with descriptive and causal approaches. Data were collected through questionnaires distributed to 100 active university students in Semarang who had previously repurchased The Originote products. The sampling technique used was purposive sampling, and the data were analyzed using SPSS version 25. The analytical tools include validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination (Adjusted R²). The results show that social media marketing and brand ambassadors have a positive and significant effect on repurchase intention, while product quality does not. Simultaneously, all three variables significantly influence repurchase intention.